Role of Effective Communication Strategy as A Veritable Tool to Deepen Trade Facilitation - Abdullahi Aliyu Maiwada (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
This paper explores the pivotal role of effective communication strategy as a veritable tool for deepening trade facilitation in contemporary global and national contexts. As countries strive to enhance cross-border trade efficiency, reduce transaction costs, and comply with international trade agreements such as the WTO Trade Facilitation Agreement, strategic communication emerges as a critical enabler of reform implementation, stakeholder engagement, and institutional transparency. The paper is anchored on Shannon-Weaver Model of Communication, Two-Way Communication Model and Stakeholder Theory. The paper argues that an effective communication strategy serves as a vital catalyst in deepening trade facilitation by streamlining the flow of information among stakeholders, minimizing misunderstandings, and promoting compliance with trade regulations. Moreover, strategic communication enhances stakeholder engagement, promotes awareness of trade benefits, and facilitates the adoption of digital trade platforms, which are crucial for efficient cross-border transactions. The paper concludes that in today’s fast-evolving global trade environment, the strategic deployment of effective communication is not just a supportive function; it is a catalyst for transformation. Effective communication is the bridge between policy and practice. When used deliberately and strategically, it strengthens institutional credibility and deepens trade facilitation in ways that drive economic growth, enhance environmental sustainability, and bolster national energy security. The future of trade is green, digital, and fast, and the time to act is now